2010
DOI: 10.1007/s12223-010-0040-7
|View full text |Cite
|
Sign up to set email alerts
|

Identification and characterization of the dominant lactic acid bacteria isolated from traditional fermented milk in Mongolia

Abstract: Five samples of Airag and 20 of Tarag (both in Mongolia) were collected from scattered households. One hundred strains of lactic acid bacteria (LAB) were isolated and identified from these samples according to phenotypic characterization and 16S rRNA gene sequence analysis. Eighty-five isolates belonged to the genus Lactobacillus, 15 being classified as coccoid LAB. All isolates belonged to 5 genera and 11 to different species and subspecies. Lactobacillus (Lb.) helveticus was predominant population in Airag s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
16
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(19 citation statements)
references
References 18 publications
2
16
0
Order By: Relevance
“…While identifying LAB from koumiss by 16S rRNA sequences, 55 strains were Lactobacillus helveticus, Lactobacillus casei, Lactobacillus plantarum, Lactobacillus delbrueckii, Enterococcus durans, Leuconostoc lactis, Leuconost mesenteroides. Similar results were found by Sun et al [10].…”
Section: Resultssupporting
confidence: 92%
See 1 more Smart Citation
“…While identifying LAB from koumiss by 16S rRNA sequences, 55 strains were Lactobacillus helveticus, Lactobacillus casei, Lactobacillus plantarum, Lactobacillus delbrueckii, Enterococcus durans, Leuconostoc lactis, Leuconost mesenteroides. Similar results were found by Sun et al [10].…”
Section: Resultssupporting
confidence: 92%
“…and Lactobacillus helveticus were isolated in most of koumiss samples. However, we reported some different results, because we found more coccoid isolates than Sun et al (2010) in koumiss. This may be due to differences in analytical condition, pH, and production technology that shape the various microbial profiles of fermented milk.…”
Section: Lab Identificationmentioning
confidence: 58%
“…Earlier studies reported the presence of the Lactobacillus plantarum and lactobacillus brevis in Sudanese fermented camel milk (Ashmaig et al, 2009). Sun et al (2010) isolated the Lactobacillus plantarum and Lactococcus lactis from traditional fermented milk in Mongolia.…”
Section: Biochemical Identification Of Lactic Strainsmentioning
confidence: 99%
“…A total of 234 lactobacilli were chosen from isolates (Table 1), which were preliminary classified and identified as L. casei group, L. plantarum group and L. acidophilus group by biochemical tests and 16S rRNA gene sequences in our laboratory [19][20][21][22].…”
Section: Bacterial Strainsmentioning
confidence: 99%